Surgical implantation and functional assessment of an invasive telemetric system to measure autonomic responses in domestic pigs. (January 2016) - Krause, A.; Zebunke, M.; Bellmann, O.; Mohr, E.; Langbein, J.; Puppe, B.
Highlights: A surgical implantation procedure was established for a telemetric system in pigs. ECG and blood pressure were measured to assess autonomic reactions. Increased behavioural activity decreased detection performance. Blood pressure signal was less susceptible to artefacts than electrocardiogram. Feeding behaviour caused a shift from autonomic balance to sympathetic dominance. Abstract: The first aim of this study was to establish a surgical procedure to implant a new telemetric device for the continuous recording of electrocardiogram (ECG) and blood pressure (BP) in freely moving pigs. A second aim was the functional assessment of cardiovascular parameters, including heart rate variability (HRV) and blood pressure variability (BPV), so that these data could be used as the basis for the objective evaluation of autonomic activity and balance in different behavioural contexts. Eleven domestic pigs (German Landrace) underwent surgery for the placement of a telemetric device. At day 15 after surgery, 512 consecutive inter-beat intervals and pressure waves were analysed using different detection methods (automatic and manually corrected) while the animals were resting or feeding, respectively. HRV and BPV were calculated. Incomplete datasets were found in four pigs due to missing ECG or BP signals. Technical and surgical issues concerning catheterisation and detachment of the negative ECG lead were continuously improved. In the remaining pigs, excellent signal quality (manually corrected data of 1%) was obtained during resting and acceptable signal quality (<10%) was obtained during feeding. Automatic triggering was sufficiently reliable to eliminate errors in BP recordings during active behaviour, but this was not the case for ECG recordings. Sympathetic arousal with accompanying vagal withdrawal during feeding was documented. The established surgical implantation and functional assessment of the telemetric system with the reliable registration of cardiovascular parameters in freely moving pigs could serve as a basis for future studies of autonomic regulation in context of stress and animal welfare.